Gender dimensions of social networks and technology adoption: Evidence from a field experiment in Uttar Pradesh - Spielman, David J.; Magnan, Nicholas (International Food Policy Research Institute, 2014)
The CSISA project was launched in 2009 with the goal of reducing food andincome insecurity in South Asia through accelerated development and deployment of new cereal varieties, sustainable crop and resource systems management practices, and better access to information. The project includes widespread delivery and adaptation of production and postharvest technologies to increase cereal production and raise income; and promotion of (i) crop and resource manag-ement practices, and (ii) high-¬yielding, stress tolerant and disease-and insect resistant rice, wheat and maize varieties and hybrids. GAAP looked at two different CSISA projects. This project focused on how gendered social networks affect how men and women within the same household acquire information about agricutural technologies, using the technology of laser land leveling (LLL) as an example.